2023
DOI: 10.3389/fpsyg.2023.1067198
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of geospatial thinking on the relationship between family capital and academic achievement in geography

Abstract: PurposeFamily environment has the major impact on children’s academic development. The aim of this study was to research the relationship between family capital and academic achievement in geography. Further, geospatial thinking, as a form of spatial thinking focusing on the scale of the geographical environment, is closely related to family environment and academic achievement in geography. Thus, the study was more specifically to apply a mediation model to explore the potential mediating role of geospatial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…This is because with the development of information technology, both males and females can equally access schema conducive to the development of spatial thinking abilities through smartphones and internet map applications [46]. Another study showed that, compared to family capital, gender does not significantly impact geospatial thinking ability [47]. However, more studies have proven that geospatial thinking ability are influenced by gender, and different researchers have varying interpretations of this.…”
Section: The Moderating Role Of Gendermentioning
confidence: 99%
“…This is because with the development of information technology, both males and females can equally access schema conducive to the development of spatial thinking abilities through smartphones and internet map applications [46]. Another study showed that, compared to family capital, gender does not significantly impact geospatial thinking ability [47]. However, more studies have proven that geospatial thinking ability are influenced by gender, and different researchers have varying interpretations of this.…”
Section: The Moderating Role Of Gendermentioning
confidence: 99%